Pelatihan Manajemen Rantai Pasok Bagi Umkm - Tina Kartini (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Supply chain management training for MSMEs aims to provide understanding and skills in managing supply chains effectively. This training covers inventory management, production processes, distribution, shipping, and logistics management. By understanding how to manage supply chains effectively, MSMEs can improve their operational efficiency, increase customer satisfaction, reduce costs, and increase profitability. This training also helps MSMEs build better relationships with their business partners, suppliers, distributors, and customers. MSMEs that have good relationships with their business partners will be more likely to get better prices, reduce supply risk, and improve their reputation in the market. The results of this training add to the knowledge and skills needed to manage supply chains effectively, help MSMEs increase profits, and build good relationships with their business partners. Supply chain management training is essential for MSMEs looking to improve the success and sustainability of their business in an increasingly competitive market.